Effect of Variation Natrium Sitrat Concentration and Centrifugation Time on Prothrombin Time (PT) Value - Najiyyah, Amalia Nur; Marliana, Nina; Hayati, Eem; Rahmat, Mamat (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Prothrombin Time (PT) test is one of the hemostasis tests used to determine whether there is a deficiency of extrinsic clotting factors and co-pathway clotting factors, namely factors I, II, V, VII, and X. The pre-analytical stage that must be considered in the hemostasis examination is the concentration of anticoagulant used and the centrifugation process. This study was conducted to determine the effect of variations in sodium citrate anticoagulant concentration and centrifugation time on Prothrombin Time (PT) values.  Method: The anticoagulants used in this study were 3.2% and 3.8% sodium citrate. Centrifugation is the process of separating cells from plasma. The effect of improper centrifugation is to increase the number of platelets, so that platelet factors contained in platelets will accelerate the formation of fibrin. The research conducted is a pseudo-experimental study by giving treatment to blood specimens that will be added with anticoagulant Sodium Citrate concentrations of 3.2% and 3.8% with a blood ratio of 9:1, then centrifuged at 3000 rpm and given a variation of time for 15 minutes, 10 minutes, and 5 minutes. The results were tested using Saphiro Wilk and Friedman Test. Result : Based on the research that has been done, the Asymp. Sig. value obtained in the Friedman Test is >0.05. This indicates that the treatment that has been given to the sample has no effect on the value of Prothrombin Time. Conclusion: It can be concluded that there is no significant difference between the variation of sodium citrate concentrations of 3.2% and 3.8%, as well as in the variation of 3000 rpm centrifugation time of 15 minutes, 10 minutes, and 5 minutes on the value of Prothrombin Time (PT).